A Modified MacCormack's Scheme (Journal of Computational Mathematics, 2021)
In this paper a modified MacCormack's scheme is presented. The scheme is based on flux vector splitting. The test computations show that the proposed modified scheme produces much better numerical results than original MacCormack's scheme.